An entrepreneurial process model from an institutional perspective: A multiple case study based on the grounded theory. Issue 2 (3rd June 2019) - SU, Yufeng; WU, Nengquan; Zhou, Xiang
Abstract : Purpose: Entrepreneurial process strongly relies on context. The previous entrepreneurship research in developed countries over-emphasizes on its economic impact, but ignores its social impact, which leads to the slow development of entrepreneurship theories. Transitioning China provides entrepreneurs with a typical environment where opportunities and constraints coexist, which is a new research area in the field of entrepreneurship study. Design/methodology/approach: Based on the grounded theory approach, this paper generalizes a local entrepreneurial process model from a multiple case study. Findings: The paper states that the interaction among entrepreneurs, opportunities and institutional context is the core of the process. To be specific, entrepreneurial process includes an inner and an outer mechanism. The inner mechanism is based on the relations among institutional constraints, entrepreneurs and opportunities: nascent entrepreneurs, forced by institutional constraints to start a business, undergo a psychological process with entrepreneurial angst, reflective learning and effectuation and finally create business opportunities. The outer mechanism is grounded in the relations among new ventures, institutional evolution and opportunity development: new ventures facilitate institutional evolution through institutional entrepreneurship strategies, which in turn supports the ventures in the sustainable development of opportunities. Originality/value: This study illuminates the social and institutional impact of entrepreneurial behavior, which is gradually fading and forgotten in modern society. The findings of the study enrich the research on entrepreneurial process, entrepreneurial cognition and institutional entrepreneurship and also provide implications for entrepreneurs.